(untitled) (Communications in Computational Physics, 2017)
The present paper follows our previous work [Yang et al., Phys. Rev. E, 90 (2014), 063011] in which the bending modes of a symmetric flexible fiber in viscous flows were studied by using a coupling approach of smoothed particle hydrodynamics (SPH) and element bending group (EBG). It was shown that a symmetric flexible fiber can undergo four different bending modes including stable U-shape, slight swing, violent flapping and stable closure modes. For an asymmetric flexible fiber, the bending modes can be different. This paper numerically studies the fiber shape, flow field and fluid drag of an asymmetric flexible fiber immersed in a viscous fluid flow by using the SPH-EBG coupling method. An asymmetric number is defined to describe the asymmetry of a flexible fiber. The effects of the asymmetric number on the fiber shape, flow field and fluid drag are investigated.